The immunomodulation role of Th17 and Treg in renal transplantation - Huang, Dan-Lei; He, Yi-Ran; Liu, Yu-Jing; He, Hong-Yu; Gu, Zhun-Yong; Liu, Yi-Mei; Liu, Wen-Jun; Luo, Zhe; Ju, Min-Jie (Frontiers in Immunology, 2023)
Kidney transplantation (KT) is an ultimate treatment of end-stage chronic kidney disease, which can meet a lot of complications induced by immune system. With under-controlled immunosuppression, the patient will obtain a good prognosis. Otherwise, allograft disfunction will cause severe organ failure and even immune collapse. Acute or chronic allograft dysfunction after KT is related to Th17, Treg, and Th17/Treg to a certain extent. Elevated Th17 levels may lead to acute rejection or chronic allograft dysfunction. Treg mainly plays a protective role on allografts by regulating immune response. The imbalance of the two may further aggravate the balance of immune response and damage the allograft. Controlling Th17 level, improving Treg function and level, and adjusting Th17/Treg ratio may have positive effects on longer allograft survival and better prognosis of receptors.